2022
DOI: 10.31790/inspilip.v5i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Enfermedad de Chagas en el Ecuador: una revisión sistemática de los aspectos epidemiológicos y entomológicos

Abstract: Chagas disease is a chronic and systemic parasitosis caused by the hemoflagellate protozoan Trypanosoma cruziandtransmittedmainlybyinsectsoftheTriatominae subfamily. Currently, at least 151 species of Triatominae are recognized, with species of the genera, Triatoma, Rhodnius and Panstrongylus, with an important epidemiological role in the transmission of the disease. In Ecuador it is difficult to know the trueepidemiological situation of this disease, its implications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Between 2013 and 2019, 10 cases were reported in children aged 1-4 years old and 11 cases in children aged 5-9. Additionally, two cases were reported in infants under 1 year old between 2015 and 2016 (33); Moreover, a study conducted in the Ecuadorian Amazon from 2015 to 2018, which analyzed the seroprevalence of CD, found nine cases in children aged 10 years old (34). In another study by Quinde-Calderón et al, which analyzed data from 2004 to 2014, a total of 915 human cases of CD were reported in Ecuador.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2013 and 2019, 10 cases were reported in children aged 1-4 years old and 11 cases in children aged 5-9. Additionally, two cases were reported in infants under 1 year old between 2015 and 2016 (33); Moreover, a study conducted in the Ecuadorian Amazon from 2015 to 2018, which analyzed the seroprevalence of CD, found nine cases in children aged 10 years old (34). In another study by Quinde-Calderón et al, which analyzed data from 2004 to 2014, a total of 915 human cases of CD were reported in Ecuador.…”
Section: Discussionmentioning
confidence: 99%